Measles Lymphadenopathy in a Child With PFAPA Syndrome. (September 2018) - Terry, Jefferson; Brown, Kelly; Hiebert, Joanne; Al-Rawahi, Ghada N; Moxham, J Paul; Krajden, Mel; Jassem, Agatha N; Tucker, Lori
Periodic fever, aphthous stomatitis, pharyngitis, and cervical adenitis (PFAPA) syndrome is a common cause of periodic fever in children. The pathogenesis of PFAPA is unknown but likely involves immune system dysregulation and may be initiated by an environmental trigger. Tonsillectomy resolves or improves symptoms in some patients, but the reason for this is unknown; moreover, specific abnormalities in tonsillectomy specimens from PFAPA patients have not been described. Here, we report measles virus in tonsil from a child with PFAPA. Measles-type viral cytopathic effect was discovered on histological examination of tonsillar tissue after therapeutic tonsillectomy for PFAPA. Molecular testing showed the left tonsil was positive for measles RNA by reverse transcription polymerase chain reaction (RT-PCR) while the right tonsil was inconclusive (weakly positive). Real-time RT-PCR specific for measles vaccine strain RNA (genotype A) was weakly reactive in the left tonsil tissue when tested in 3 independent replicates, but this result could not be confirmed with conventional genotyping by sequencing. The relationship and clinical significance between measles virus and PFAPA in this case is unclear but may be related to PFAPA-associated immune dysregulation. Additional investigation of measles virus in PFAPA patients would be helpful in further exploring this potential association.